The influence of air pollution on asthma in athletes – a brief review of the literature - Kruczyk, Barbara; Piętak, Mateusz; Stradczuk, Monika; Mazurek, Łukasz; Czach, Zuzanna; Bachurska, Dominika; Rękas, Barbara; Mazurek, Wojciech; Olędzka, Joanna; Kopacz, Wojciech (Quality in Sport, 2024)
Introduction and purpose Air pollution, stemming from natural occurrences and human activities, significantly threatens global health, particularly impacting respiratory conditions like asthma. Air pollution substantially influences asthma exacerbation in athletes, a group particularly vulnerable due to their high physical activity levels and increased respiratory demands. Key pollutants, including particulate matter (PM), ground-level ozone (O3), sulfur dioxide (SO2), and nitrogen dioxide (NO2), play critical roles in asthma development and exacerbation. The State of Knowledge Asthma, a chronic inflammatory disease influenced by genetic predisposition and environmental factors like air pollution, is characterized by airway hyperresponsiveness, obstruction, and chronic inflammation, leading to symptoms such as shortness of breath, coughing, wheezing, and chest tightness. Research highlights the link between air pollution exposure and asthma development, with PM2.5 exposure associated with increased asthma risk and pollutants exacerbating symptoms, especially in children. Athletes inhaling air pollutants during exercise face increased airway inflammation, mucus production, and bronchospasm, worsening asthma symptoms like wheezing and shortness of breath. Chronic exposure decreases lung function, increasing reliance on medication and limiting outdoor training on polluted days. Summary Effective asthma management amidst air pollution requires personal, community, and governmental measures. Patients should minimize exposure by wearing N95 masks and choosing low-traffic routes. Governments must monitor pollution, inform the public, and control emissions through alternative fuels and technologies. Adhering to WHO air quality guidelines could prevent many new asthma cases, emphasizing comprehensive air quality management's importance, especially among vulnerable populations like children.